From fear to eternity : an immortality bites mystery - Rowen, Michelle (Rowen, Michelle. Immortality bites series., 2014)
While attending an auction of paranormal objects, newlywed vampires Sarah and Thierry discover that an amulet containing a wish-granting djinn has fallen into the wrong hands, trapping them in a world where they must be careful what they wish for.